The anti-infective outcomes of the distal femoral replacement coated with antibiotic cement in limb salvage surgery: A randomized clinical trial. Issue 4 (28th January 2022) - Shi, Lei; Tang, Zhen; Tao, Pengfei; Li, Xiaokang; Guo, Shuo; Wei, Xinghui; Yu, Xiaodi; Liu, Wenwen; Guo, Zheng
Abstract: Background: The aim of this study was to observe the anti-infective effect of the distal femoral tumor prosthesis coated with antibiotic cement during limb salvage treatment, and evaluate its potential prospect in clinic. Methods: In this randomized controlled trial, the en bloc resection and reconstruction were performed in 36 patients with distal femoral primary bone tumor. Patients were divided into 2 groups randomly according to the application of antibiotic bone cement coating, which included antibiotic cement coating group (16 cases) and control group (18 cases). There were 10 men and 6 women in anti-infection group, aged from 18 to 54 years (23.47 ± 3.53), and there were 12 men and 6 women in control group, aged from 19 to 56 years (24.16 ± 4.32). The tumor type, age, sex, and Enneking stage were enrolled with well-matched of the 2 groups of patients. There was no difference between bundles and routine standard care for each group. The antibiotic cement was coated on the surface of polyethylene jacket with punched holes during operation. The peri-prosthetic infection, local recurrence and distant metastasis were followed up and limb functions were evaluated by Musculoskeletal Tumor Society 93 (MSTS93) scoring system. Results: Patients were followed up till 34.7 months (range 18∼62 months). There was no periprosthetic infection in anti-infection group. Four cases in control group showed deep infection. Infection rate had significant differences between the 2 groups ( P < .05). Infection-related prosthesis mortality was 0% (0/16) in anti-infection group and 16.67% (3/18) in control group. Local recurrence and distant metastasis occurred in 7 of 34 patients with primary malignant bone tumor, wherein 2 cases of local recurrence and 1 cases of distant metastasis occurred in anti-infective group; 2 cases of local recurrence and 2 cases of distant metastasis occurred in the control group. During a latest follow-up, MSTS93 function scoring revealed a mean of 25.6 ± 4.2 in anti-infection group and 18.5 ± 3.3 in control group. The survival rate of anti-infective group is 75%, and the survival rate of control group is 61.11%. Conclusion: The antibiotic cement-coated technique on the surface of the polyethylene jacket of custom-made distal femoral prosthesis is simple and effective in controlling the periprosthetic infection after tumor prosthesis reconstruction.